1997
DOI: 10.1002/art.1780400213
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tenidap on the progression of osteoarthritic lesions in a canine experimental model. Suppression of metalloprotease and interleukin‐1 activity

Abstract: Objective. To study, in vivo, the therapeutic effectiveness of tenidap, an antirheumatic drug, on the progression of lesions in an experimental osteoarthritis (OA) dog model. The action of tenidap on the activity and expression of metalloproteases in cartilage, as well as on the bioactivity of interleukin-1 (IL-1) in synovial fluid, was determined.Methods. The anterior cruciate ligament of the right stifle joint of 20 mongrel dogs was sectioned through a stab wound. Dogs were divided into 3 groups: group I (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…It has been previously shown that cyclooxygenase activity accompanied by prostaglandin production could modulate the induction of inflammatory mediators such as cytokines, iNOS and MMP-9 (Minghetti et al, 1996;Fernandes et al, 1997). In the present study, we observed that Cd-induced ICAM-1 expression was significantly attenuated by NSAIDs, which was reversed by addition of exogenous PGE 2 , demonstrating the role of COX-2 in CNS inflammation.…”
Section: Discussionsupporting
confidence: 70%
“…It has been previously shown that cyclooxygenase activity accompanied by prostaglandin production could modulate the induction of inflammatory mediators such as cytokines, iNOS and MMP-9 (Minghetti et al, 1996;Fernandes et al, 1997). In the present study, we observed that Cd-induced ICAM-1 expression was significantly attenuated by NSAIDs, which was reversed by addition of exogenous PGE 2 , demonstrating the role of COX-2 in CNS inflammation.…”
Section: Discussionsupporting
confidence: 70%
“…The extent of the effects was similar to that previously demonstrated with intraarticular steroid injections in this model (22,37) and with tenidap (38), an antiinflammatory drug, which potently inhibited COX as well as the synthesis of proinflammatory cytokines including IL-1␤ and IL-6 (39). The inhibition of IL-1␤ synthesis/action seemed to be of particular importance to the effectiveness of these drugs in reducing the development of OA in the dog model (24,40).…”
Section: Discussionsupporting
confidence: 67%
“…The extent of reduction in the severity of cartilage structural changes induced by ML-3000 in this OA model was similar to that previously reported to occur with tenidap (38). At the histologic level, the effect of the drug was characterized by a significant decrease in the severity of changes for all OA histologic criteria, including cartilage structure, cell morphology, and intensity of Safranin O staining.…”
Section: Discussionsupporting
confidence: 66%
“…Yet, SF IL-1 bioactivity is only found in 8% of the samples (Carter et al, 1999). In dogs with experimentally transected CrCL (Pond-Nuki model), bioactivity of IL-1 varied from undetectable to increased in the operated stifle joints (Carter et al, 1999;Fernandes et al, 1997). Significant higher levels were found by bioassay in the SF of dogs with naturally occurring CrCL rupture compared with SF of normal dogs (Fujita et al, 2006).…”
Section: Pro-inflammatory Cytokinesmentioning
confidence: 99%